Cognitive impairment in syphilis: Does treatment based on cerebrospinal fluid analysis improve outcome? - Arielle P Davis (Public Library of Science (PLoS), 2021)
Background Individuals with previous syphilis may experience cognitive impairment. The goal of this study was to determine if those at high risk for laboratory-defined neurosyphilis are cognitively impaired, and whether treatment based on cerebrospinal fluid (CSF) findings results in better outcomes. Methods Participants had a new syphilis diagnosis, serum RPR titer ≥ 1:32 or peripheral blood CD4+ T cells ≤ 350/ul (in persons living with HIV) and did not endorse neurological symptoms. They underwent computerized cognitive assessment with the CogState. Thirty-two were randomized to either undergo lumbar puncture (LP) or to not undergo LP and 14 underwent LP; 64 were not randomized and 48 opted to undergo LP. Results Demographics, cognitive complaints and cognitive impairment did not differ between randomized and nonrandomized participants. Two-thirds were cognitively impaired, and impairment was not more common in those with cognitive complaints. The adjusted odds of increased severity of impairment were 3.8 times greater in those with CSF pleocytosis compared to those without. Time to cognitive normalization, improvement or decline did not differ between those who did not undergo LP and those who underwent LP and whose treatment was based on CSF analysis. Taking into account pre-treatment cognitive impairment, the risk of cognitive decline was lower in those with CSF pleocytosis treated for neurosyphilis compared to those without CSF pleocytosis not treated for neurosyphilis, (HR 0.24 (95% CI 0.07-0.88], p = 0.03). Conclusion In individuals at high risk for laboratory-defined neurosyphilis, cognitive complaints are not a good indicator of cognitive impairment. Severity of cognitive impairment was greater in those with CSF pleocytosis. Identification and treatment of those with neurosyphilis may mitigate subsequent cognitive decline.